Dysregulated T cells in multiple sclerosis. (8th March 2018) - Chihara, Norio
Abstract: Multiple exogenous signals received from cell surface molecules or cytokines play a significant role in altering the host immune response. In chronic autoimmune‐mediated diseases, such as multiple sclerosis (MS), immune cells, especially T cells, are involved in the long‐term pathophysiology. In the past few decades, mechanisms of pathogenic T‐cell involvement at the onset or relapse of disease have been highlighted. However, the factors controlling the disease course have yet to be elucidated because of the complexity of tissue environmental factors. In contrast, dysfunctional or exhausted T cells have been identified as distinct cell lineages in chronic inflammatory diseases, such as cancer or chronic viral infections that show regulatory T cell phenotypes; for example, expressing high levels of co‐inhibitory receptors. Regarding cell surface molecule expression, while co‐stimulatory molecules promote effector T‐cell function, co‐inhibitory molecules promote regulatory T‐cell function, limiting the inflammatory response. In MS, augmented activation of effector T cells as a result of the impairment of regulatory T‐cell function has been implicated. Thus, a comparison between these regulatory T cells in MS and dysfunctional T cells in cancer could provide clues to understand the mechanism of dysregulated T cells, resulting in sustained immune reactions in the long‐term disease course of MS. Furthermore, this reveals new immunomodulatory strategies to regain regulatory T‐cell function in MS.